Three-dimensional analysis for square seismic isolation bearings under large shear deformations and high axial loads. - Kikuchi, Masaru
Square seismic isolation bearings are economical to manufacture, offer the advantage of simple connection configurations and have compact geometry requiring a minimum of space for installation. To be able to more effectively utilize square bearings for seismic isolation systems, a new mechanical model for predicting the large shear deformation behavior of square elastomeric isolation bearings is presented in this paper. The new model is developed by extending to three dimensions an existing model for elastomeric isolation bearings under severe axial loads and shear deformations. The model comprises multiple shear springs at the mid-height and a series of axial springs at the top and bottom boundaries. Static loading tests of square lead?rubber isolation bearings were performed to investigate the influence of horizontal loading direction and axial load magnitude on bearing behavior. The test results showed that the ultimate behavior is strongly influenced by loading direction, especially under large shear deformation and high axial load. To confirm the validity of the model, analyses are performed of the loading tests of the square lead?rubber isolation bearings. The results of analyses using the new model show very good agreement with the experimental results.
Keywords: Seismic isolation; Square elastomeric isolation bearing; Large shear deformation; High axial load; Nonlinear hysteresis model; Three-dimensional.